Efficacy and Safety of High-dose versus Standard-dose Prazosin in Paediatric Scorpion Envenomation: A Single-blinded Randomised Controlled Study - Apoorva Gayatri Abbadi; Hidaytullah R Bijapure; Chandrika R Doddihal; Bhavana B Lakhkar; Y Rohith; VJ Prakash; Kumar BM Prasanna; Mallanagouda Patil (Journal of Clinical and Diagnostic Research)
Introduction: Scorpion sting is a serious health problem in the world, especially in developing countries like India. It is often associated with serious clinical manifestations. As children have a small body surface area, they are prone to more serious cardiac, respiratory and neurological complications. Prazosin, an alpha-blocker, is the drug of choice for the treatment of scorpion envenomation. With the increasing incidence of paediatric scorpion envenomation in rural India, there is a need to optimise prazosin dosing protocols to improve outcomes and reduce hospital stays. Aim: To evaluate and compare the efficacy and safety of standard-dose versus high-dose prazosin protocols in managing paediatric scorpion envenomation in a tertiary care hospital in North Karnataka, India. Materials and Methods: A single-blinded randomised controlled study was conducted in Paediatric Intensive Care Unit (PICU) at BLDE DU Shri BM Patil Medical College Hospital and Research Centre, Vijayapur, Karnataka, India, from January 2017 to December 2022. Children below 18 years of age admitted to the hospital with history of scorpion sting with severity grades II and III were enrolled. Children were randomised into three groups: Group A: 30 μg/kg every three hours; Group B: 60 μg/kg initially, followed by 30 μg/kg every three hours; and Group C: 90 μg/kg initially, followed by 30 μg/kg every three hours. They were monitored for sweating, cold or warm extremities, the appearance and disappearance of pain, vital parameters and priapism (in male children) hourly until stabilised, then every third hourly for 24 hours and then sixth hourly til discharged from the PICU. After the patient was haemodynamically stable for 24 hours shifted to a high-dependency unit. The time interval between sting and treatment, various vital parameters, duration of the PICU stay and hospital stay were noted. Categorical variables were compared using the Chi-square test and continuous variables were analysed using the Student’s t-test. Results: A total of 86 children were recruited. The standard protocol (Group A) had 26, Group B had 29 and Group C had 31 children. Forty-eight (56%) of the children were over five years old (12, 21 and 15 were in Groups A, B and C, respectively). The male-to-female ratio of 1.8:1, 2.6:1 and 1.8:1 in Groups A, B and C, respectively. The sting-to-symptom interval, priapism, duration of hypertension and duration of hospital stay were higher in Group B compared to Group A. The duration of hypertension, cardiac involvement and priapism were higher in Group C, whereas a shorter sting-to-symptom interval and symptom-to-prazosin initiation were noted in Group C compared to Group A. Conclusion: High-dose prazosin is a safe and effective treatment for scorpion envenomation in children, offering a potential advantage over the standard dosing protocol.